Contribution of Gram Panchayats in Rural Development: A Study of Shri Chandpura, Nayagaon Bolka, Thana Rajaji and Kaleshan Gram Panchayats of Alwar District: ग्रामीण विकास में ग्राम पंचायतों का योगदान: अलवर जिले की श्रीचन्दपुरा, नयागांव बोलका, थाना राजाजी और कलेशान ग्राम पंचायतों का अध्ययन - Verma, Jitendra Kumar; Meena, Mahendra Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The condition of India’s villages deteriorated significantly during British rule. After gaining independence, the decentralization of political and economic power in villages was achieved through the Panchayati Raj system. The Balwant Rai Mehta Committee recommended a three-tier structure for Panchayati Raj, including Gram Panchayats, Block Committees, and District Councils. This study analyzes the Gram Panchayats of Shri Chandpura, Nayagaon Bolka, Thana Rajaji, and Kaleshan in Alwar district. These Panchayats are now receiving necessary powers and funds, leading to visible prosperity in the villages. The research examines the issues faced by the Secretary, Sarpanch, and other officials under the Panchayati Raj, particularly financial difficulties and the challenges in implementing government schemes. Abstract in Hindi Language: भारत के गाँवों की दशा ब्रिटिश शासन के दौरान बहुत खराब हो गई थी। स्वतंत्रता प्राप्ति के बाद पंचायती राज व्यवस्था के माध्यम से गाँवों में राजनीतिक और आर्थिक सत्ता का विकेंद्रीकरण किया गया। बलवन्त राय मेहता समिति ने पंचायती राज के लिए त्रि-स्तरीय योजना की सिफारिश की, जिसमें ग्राम पंचायतें, क्षेत्र समितियाँ, और जिला परिषदें शामिल हैं। इस अध्ययन में अलवर जिले की श्रीचन्दपुरा, नयागांव बोलका, थाना राजाजी और कलेशान ग्राम पंचायतों का विश्लेषण किया गया है। इन पंचायतों को आवश्यक अधिकार और धन मिल रहा है, जिससे गाँवों में समृद्धि दिखने लगी है। इस शोध में पंचायती राज के अंतर्गत सचिव, सरपंच, और अन्य पदाधिकारियों की समस्याओं और पंचायत के कार्यों में आने वाली वित्तीय कठिनाइयों का विश्लेषण किया गया है। Keywords: सत्ता का विकेंद्रीकरण, पंचायती राज, ग्राम पंचायत, वित्तीय समस्या।